EVALUATION OF USER EXPERIENCE TLX TRAINING GATE FOR COMPETITIVE PROGRAMMING LEARNING USING USER EXPERIENCE QUESTIONNAIRE AND SYSTEM USABILITY SCALE - Guntur Eka Saputra; Rakhmi Khalida; Ratu Nurmalika (International Journal Science and Technology, 2022)
Usability is a measurement of software applications to determine how easy the software is. Usability testing is done by involving end users or it can also involve experts. User Experience Questionnaire (UEQ) and System Usability Scale (SUS) are two approaches that can be used to measure Usability. Based on the provisions for determining the results of the SUS assessment, the percentile rank score, which is seventy-five, the results of the respondents' assessment on the TLX Training Gate application, the user acceptance level is in the acceptable category, the scale grade level is in category C, and the rating adjective is in the good category and with UEQ approach There are 3 (three) scales in the Above Average range and 2 (two) scales still below average, and 1 on the good scale. The result of the stimulation score (1,35) and attractiveness (1,27) because this system is attractive and comfortable for students so that the value of this aspect has a positive impression. Based on research, for 6 (six) aspects this shows that system development is needed so that students as users can maximize their learning potential in competitive programming learning